“A Vast and Beautiful Country”: Ideas of Exile, Racial Hierarchies, and Industrial Education in the Formation of the American Presbyterian Congo Mission (APCM) and the Congo Free State (CFS), 1832-1890 - Reuben Loffman (Revista de História da Sociedade e da Cultura)
Recent literature has highlighted the close relationship between the American Presbyterian Congo Mission (APCM) and the government of the Belgian Congo. Despite a libel trial in 1909, which saw the APCM face a key Belgian ally in court, historians, such as Ira Dworkin and Simon Mbau, have emphasised their co-operation following the dispute. This article adds to literature on the APCM and Belgian imperialism by exploring the beliefs they shared during their formative years and so well before the trial. While there were differences in their approaches to African societies, both saw what they considered “civilization” emanating from a core of white, male elites. Léopold II and the APCM’s allies also wanted to exile those who challenged their privileges at home to the Congo. Finally, the APCM became well placed to facilitate the Belgian regime’s later appetite for industrial education as it was important in many of its missionaries early schooling.